Download presentation

Presentation is loading. Please wait.

Published byAshlee Conley Modified over 9 years ago

1
3.2 Solving Systems Algebraically 2. Solving Systems by Elimination

2
2) Solving Systems by Elimination By adding and subtracting linear systems, you can “eliminate” a variable and solve for an unknown

3
2) Solving Systems by Elimination Example 1: Solve the system by elimination. 4x + 3y = 4 2x – y = 7 {

4
2) Solving Systems by Elimination Example 1: Solve the system by elimination. 4x + 3y = 4 2x – y = 7 { Elimination – add or subtract the equations of a linear system until you “eliminate” a variable

5
2) Solving Systems by Elimination Example 1: Solve the system by elimination. 4x + 3y = 4 1 2x – y = 7 2 Step 1: Number the equations. {

6
2) Solving Systems by Elimination Example 1: Solve the system by elimination. 4x + 3y = 4 1 2x – y = 7 2 Step 2: Multiply one or both equations to make the coefficient in front of x OR y the same in both equations. {

7
2) Solving Systems by Elimination Example 1: Solve the system by elimination. 4x + 3y = 4 1 2x – y = 7 2 multiply by 2 Step 2: Multiply one or both equations to make the coefficient in front of x OR y the same in both equations. {

8
2) Solving Systems by Elimination Example 1: Solve the system by elimination. 4x + 3y = 4 1 2x – y = 7 2 multiply by 2 4x – 2y = 14 Step 2: Multiply one or both equations to make the coefficient in front of x OR y the same in both equations. { 2

9
2) Solving Systems by Elimination Example 1: Solve the system by elimination. 4x + 3y = 4 1 2x – y = 7 2 multiply by 2 4x – 2y = 14 Step 3: Equation subtract { 221

10
2) Solving Systems by Elimination Example 1: Solve the system by elimination. 4x + 3y = 4 4x – 2y = 14 Step 3: Equation subtract 2112 - Use subtraction to eliminate x

11
2) Solving Systems by Elimination Example 1: Solve the system by elimination. 4x + 3y = 4 4x – 2y = 14 5y = -10 y = -2 Step 3: Equation subtract 2112 -

12
2) Solving Systems by Elimination Example 1: Solve the system by elimination. 4x + 3y = 4 4x – 2y = 14 5y = -10 y = -2 Step 4: Use substitution to solve for the remaining unknown. 12 -

13
2) Solving Systems by Elimination Example 1: Solve the system by elimination. 4x + 3y = 4 Sub y = -2 into 4x + 3(-2) = 4 4x – 6 = 4 4x = 10 x = 2.5 Step 4: Use substitution to solve for the remaining unknown. 11

14
2) Solving Systems by Elimination Example 1: Solve the system by elimination. Therefore, the solution is (2.5, -2).

15
2) Solving Systems by Elimination Example 2: Solve the system by elimination. x + 6y = 2 5x + 4y = 36 {

16
2) Solving Systems by Elimination Example 2: Solve the system by elimination. x + 6y = 2multiply by 5 5x + 4y = 36 { 1 12

17
2) Solving Systems by Elimination Example 2: Solve the system by elimination. x + 6y = 2multiply by 5 5x + 4y = 36 becomes… 5x + 30y = 10 { 1 121

18
2) Solving Systems by Elimination Example 2: Solve the system by elimination. x + 6y = 2multiply by 5 5x + 4y = 36 becomes… 5x + 30y = 10 subtract { 1 12112

19
2) Solving Systems by Elimination Example 2: Solve the system by elimination. 5x + 30y = 10 5x + 4y = 36 1 12 -

20
2) Solving Systems by Elimination Example 2: Solve the system by elimination. 5x + 30y = 10 5x + 4y = 36 26y = -26 y = -1 1 12 -

21
2) Solving Systems by Elimination Example 2: Solve the system by elimination. 5x + 30y = 10 5x + 4y = 36 26y = -26 y = -1Sub y = -1 in either equation. 1 12 -

22
2) Solving Systems by Elimination Example 2: Solve the system by elimination. 5x + 4y = 36 5x + 4(-1) = 36 5x – 4 = 36 5x = 40 x = 8 1 2

23
2) Solving Systems by Elimination Example 2: Solve the system by elimination. x + 6y = 2 5x + 4y = 36 Therefore, the solution to the system is (8, -1). {

24
2) Solving Systems by Elimination Example 2: Solve the system by elimination. x + 6y = 2 5x + 4y = 36 Check: 8 + 6(-1) = 25(8) + 4(-1) = 36 2 = 2 36 = 36 {

25
2) Solving Systems by Elimination Example 3: Solve each system by elimination. a) -3x + 5y = 7b) 2x – 3y = 18 6x – 10y = -14 -2x + 3y = -6 {{

26
2) Solving Systems by Elimination Example 3: Solve each system by elimination. a) -3x + 5y = 7b) 2x – 3y = 18 6x – 10y = -14 -2x + 3y = -6 {{ Multiply by 2

27
2) Solving Systems by Elimination Example 3: Solve each system by elimination. a) -6x + 10y = 14b) 2x – 3y = 18 6x – 10y = -14 -2x + 3y = -6 0x + 0y = 0 0x + 0y = 12 0 = 0 0 = 12 {{ + +

28
2) Solving Systems by Elimination Example 3: Solve each system by elimination. a) -6x + 10y = 14b) 2x – 3y = 18 6x – 10y = -14 -2x + 3y = -6 0x + 0y = 0 0x + 0y = 12 0 = 0 0 = 12 {{ Always true. The equations represent the same line. The system is dependent. There is an infinite number of solutions. + +

29
2) Solving Systems by Elimination Example 3: Solve each system by elimination. a) -6x + 10y = 14b) 2x – 3y = 18 6x – 10y = -14 -2x + 3y = -6 0x + 0y = 0 0x + 0y = 12 0 = 0 0 = 12 {{ Never true. The equations represent parallel lines. The system is inconsistent. There is no solution. + + Always true. The equations represent the same line. The system is dependent. There is an infinite number of solutions.

30
2) Solving Systems by Elimination Example 3: Solve each system by elimination. a) -6x + 10y = 14b) 2x – 3y = 18 6x – 10y = -14 -2x + 3y = -6 0x + 0y = 0 0x + 0y = 12 0 = 0 0 = 12 {{ Never true. The equations represent parallel lines. The system is inconsistent. There is no solution. + + Always true. The equations represent the same line. The system is dependent. There is an infinite number of solutions. Homework p.128 #18-21, 33, 36, 46, 55, 56, 57, 62

31
Homework p.128 #18-21, 33, 36, 46, 55, 56, 57, 62 Tomorrow: In-class assignment…come prepared!

Similar presentations

© 2024 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google